A study of procurement practices in Social Safety Net Projects of The Department of Social Services (DSS) under the Ministry of Social Welfare (MSW), Bangladesh - Kabir, Jahangir (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2020.